Analisis Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Ptpn Ix Pabrik Gula Tasikmadu - Ramadhan, Mahardhika Gilang; , Lukman Hakim, S.E., M.Si (2016)
This research was conducted in PG. Tasikmadu which aims to determine the influence of organizational culture and work environment to employees performance at PG. Tasikmadu. In this research has the objective to analyze the influence of organizational culture on employee performance, and the work environment influence on employee performance. In this test the sample with a stratified random sample, data types and sources of data used in this study using primary data obtained from the respondents' answers in the form of filling the questionnaire of employee PG. Tasikmadu. The test instrument used to test the feasibility of a question is Test Validity and Test Reliability. For the method of data analysis used in this study, the authors used multiple analysis reinforced with Normality Test, Test Multicollinearity, Heteroskidastity Test, test F and test t. The results showed that the variables of organizational culture and working environment together positive effect on employee performance significantly, the influence of organizational culture and organizational environment on the performance of employees is 55.1%. In addition to the organizational culture and work environment, employee performance were also determined by other factors not examined in this study.